Information Revelation through Option Exercise - Grenadier, Steven R. (Review of Financial Studies, 1999)
[In many real-world situations, agents must formulate option exercise strategies with imperfect information. In such a setting, agents may infer the private signals of other agents through their observed exercise strategies. The building of an office building, the drilling of an exploratory oil well, and the commitment of a pharmaceutical company toward the research of a new drug all convey private information to other market participants. This article develops an equilibrium framework for option exercise games with asymmetric private information. Many interesting aspects of the patterns of equilibrium exercise are analyzed. In particular, informational cascades, where agents ignore their private information and jump on the exercise bandwagon, may arise endogenously.]